PLD.25 Failed Regional Anaesthesia in Morbidly Obese Patients. (9th June 2014) - Isdale, M; Dickson, M; Duncan, A; Yakoub, R
Abstract : Background: Maternal obesity is associated with significantly higher chance of emergency caesarean section. Anaesthesia in such patients is technically challenging and associated with higher complication rates including death in the most extreme circumstances. We investigated the incidence of morbid obesity in failed regional anaesthesia due to inadequate blocks or failed citing. Methods: We carried out data collection of failed regional anaesthetics retrospectively over a period of eighteen months in obstetric theatres at Royal Oldham Hospital. This included patients' demographics including BMI and reasons behind failed anaesthesia. Results: 27 patients had failed regional anaesthesia. Of these, 16 (59%) had failed anaesthetics due to difficulties in citing, while 11 (41%) were due to inadequate block. 81% (13/16) of patients in whom the regional anaesthesia could not be cited and 48% (5/11) were morbidly obese (BMI >30 kg/m 2 ). Conclusion: The incidence of failed regional anaesthesia due to difficult citing is higher in patients with morbid obesity hence subsequent increased incidence of conversion to general anaesthesia. This exposes patients to potentially life-threatening risks including difficult airway management in addition to detrimental fetal effects. We recommend considering elective caesarean section in patients with morbid obesity with involvement of the anaesthetic team well in advance. This would allow appropriate imaging to be used to establish adequate regional anaesthesia in a non time-pressured environment, thus improving outcomes.